2004
DOI: 10.1167/iovs.03-0646
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Standard Automated Perimetry and GDx VCC Measurements

Abstract: GDx VCC measurements of the peripapillary RNFL relate well with functional loss in glaucoma. Based on the observed relationships between function and structure, patients with mild to moderate visual field loss in glaucoma may be better monitored with the GDx VCC and patients who have severe loss, with SAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 31 publications
4
80
1
3
Order By: Relevance
“…Many reports showed that with respect to SLP with fixed compensation (GDx-FCC), the use of variable compensation (GDx-VCC) improves significantly the structure-function relationship 5 and diagnostic ability in glaucomatous eyes. [6][7][8][9][10][11][12][13][14] Moreover, early RNFL thinning in perimetrically unaffected fellow eyes of patients with unilateral glaucoma was detected. 15 However, some eyes had to be discarded from these studies because an atypical pattern of retardation (APR) appeared on the retardation map available in the printout.…”
Section: Introductionmentioning
confidence: 90%
“…Many reports showed that with respect to SLP with fixed compensation (GDx-FCC), the use of variable compensation (GDx-VCC) improves significantly the structure-function relationship 5 and diagnostic ability in glaucomatous eyes. [6][7][8][9][10][11][12][13][14] Moreover, early RNFL thinning in perimetrically unaffected fellow eyes of patients with unilateral glaucoma was detected. 15 However, some eyes had to be discarded from these studies because an atypical pattern of retardation (APR) appeared on the retardation map available in the printout.…”
Section: Introductionmentioning
confidence: 90%
“…To calculate the mean VF loss in these six areas, the anti-log values at all single test positions were calculated and then averaged. 8,9 For presentation and statistical analyses, these averaged values were converted back to the dB scale. 9 Hood et al 4 suggest that it is important to anti-log SAP values before averaging the values.…”
Section: Vf Testmentioning
confidence: 99%
“…8,9 For presentation and statistical analyses, these averaged values were converted back to the dB scale. 9 Hood et al 4 suggest that it is important to anti-log SAP values before averaging the values. On the basis of the knowledge that underlying ganglion cell number and differential light sensitivity expressed as 1/Lamberts has a linear relationship (r 2 ¼ 0.73), 24 they provided the following rationale for antilogging SAP values before averaging them.…”
Section: Vf Testmentioning
confidence: 99%
See 2 more Smart Citations